Enhanced Fenton-like catalytic performance of N-doped graphene quantum dot incorporated CuCo2O4. (4th May 2018) - Nekoeinia, Mohsen; Salehriahi, Farideh; Moradlou, Omran; Kazemi, Hojjat; Yousefinejad, Saeed
Abstract : In the present study, a novel nanocomposite based on CuCo2 O4 and N-doped graphene quantum dots (N-GQDs) as an iron-free heterogeneous Fenton-like catalyst was prepared by a two-step solvothermal method. Abstract : In the present study, a novel nanocomposite based on CuCo2 O4 and N-doped graphene quantum dots (N-GQDs) as an iron-free heterogeneous Fenton-like catalyst was prepared by a two-step solvothermal method. The surface morphology, chemical structure, crystal phase, surface area and pore size distribution of the synthesized nanocomposite were characterized by field-emission scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy (EDS), Fourier Transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), high resolution transmittance electron microscopy (HRTEM) and N2 adsorption–desorption analysis. The results showed that the N-GQDs play a significant role in the enhancement of the catalytic degradation of methylene blue (MB) as a model contaminant. The CuCo2 O4 /N-GQD nanocomposite exhibited a higher degradation rate of about 47 times higher than that of pristine CuCo2 O4 . This promotion can be attributed to the higher surface area of the CuCo2 O4 /N-GQD nanocomposite compared to pristine CuCo2 O4 as well as the synergistic effects between the N-GQDs and CuCo2 O4 . The effects of pH, catalyst mass and the initial concentration of H2 O2 on the catalytic degradation of MB were investigated using Box–Behnken design. Finally, the dominant reactive oxygen species generated in the degradation process were identified and the possible mechanism of the catalytic degradation of MB was proposed.